Pretreatment Of Ricebran For Effective Production Of Cellulase By Aspergillus Niger - A.SRIDEVI; S.RADHA; G.NARASIMHA (International Journal of Pharma and Bio Sciences, 2011)
Rice bran a chiefly available agricultural lignocellulosic waste was pretreated with both acid (HCl) and alkaline (NaOH) at concentrations from 1N to 3N and 1N to 15N respectively, for a residence time from 10 to 30 min at 121°C for delignification of lignin from lignocellulose. The pretreatments were evaluated based on percentage of total lignin removal from lignocelluloses. Up to 73.26% and 54.50% lignin removal were observed in 10N NaOH and 1N HCl respectively. The optimum amount of sugars (4.973 mg g-1) and protein (4.760 mg g-1) were observed with 5N Sodium hydroxide treatment with 10 min of steaming. Acidic pre-treatment of rice bran resulted in peak concentrations of sugars (3.410 mg g-1) with 1N HCl and protein (3.3 mg g-1) with 2N HCl with steaming period of 10 min. The pretreated lignocellulose with different concentrations from 0.5% to 2% were used as substrate for cellulase production by fungal culture Aspergillus niger. The yield of the enzyme was reached maximum with Fpase, CMCase and b-glucosidase were 9.3, 8.5 and 1.14U/ml respectively.